ANALISIS BUDAYA SEKOLAH DALAM MENINGKATKAN DISIPLIN SISWA DI KELAS XI SMK NEGERI 1 LOLOWA’U - Darmanto Ndruru (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2023)
This research is motivated by low student discipline. This is due to the lack of strict school discipline, for example students are often late, students often dress impolitely, students often do not attend school, students smoke in the school environment and students often play truant. The purpose of this study was to find out how school culture in improving student .discipline in class XI SMK Negeri 1 Lolowa'u. The type of research used is qualitative research with a descriptive .approach. Data were collected using observation, interviews and documentation. The results .showed that school culture can improve student discipline through the habits and regulations that .exist in the school. Students are obedient and obedient to the values that are believed to be their responsibility. Through school culture such as school rules and activities formed by the school, it can improve student discipline and the formation of good student character. The conclusion of the research is that school culture is very important in providing encouragement to students so that students remain .enthusiastic in having good behavior and studying well so as to produce disciplined students. Suggestions, teachers are expected to pay more attention to student discipline in the school environment and outside school through activities or regulations that exist within the school, teachers are expected to continue to work with parents in improving student discipline.